Controlling entry in soft rock with natural support strength, strikesill, etc - 王有俊 赵庆彪 孙利中 (Journal of coal science & engineering, China, 2008)
Presented the concept of the natural support strength. The natural support strength, the strike sill, the multifunction retractors （developed by the author） and etc. were used with the technical measures to change the passive support to the initiative support, and the soft rock entry was supported. And its process is simple and less equipment is needed, and the cost is low and the advance rate is high, which can meet the requirements of actual mining. It solves many support difficult problems.